Well done, the naughtiest girl - Digby, Anne.; Blyton, Enid. (b, 2005)
"Elizabeth is desperate to play the piano in the end of school concert. But only one girl can be chosen and her rival Arabella is practising hard! Elizabeth knows Arabella is very good and might well be picked to play on the day - so, ignoring her looming exams, she spends every waking minute practicing. When Arabella is still chosen over her, she realises that not only will she not have a place in the school concert, she might well also fail all her exams. Racing to get her revision done, she finds a quiet spot in an old oak tree in the school grounds. It's very peaceful and lots of birds and other animals make their home in the tree. So when Elizabeth realises the tree is marked as one to be chopped down, she's determined not to let it happen. But can she save the tree AND manage to pass all her exams? It's going to be a fight to the finish ..."
Keywords: Allen, Elizabeth (Fictitious character) -- Juvenile fiction; Boarding schools -- Juvenile fiction; Allen, Elizabeth (Fictitious character).